2022
DOI: 10.21638/spbu16.2022.301
|View full text |Cite
|
Sign up to set email alerts
|

Ideas about real and digital worlds as part of the current worldview of adolescents and parents in a digital society: Possibilities for adaptation

Abstract: The introduction of digital devices into all spheres of life has led to a significant restructuring of our everyday life and the world of the modern person. The real world is increasingly and actively extended by the digital environment, forming a historically unique life in a mixed online and offline reality. Psychology still lacks analyses of the worldview of adolescents most actively socialized in real and virtual spaces and comparisons with perceptions of elder generations that would contribute to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Transformations related to the perceptual side of communication are of great interest. Research (Belinskaia, & Gavrichenko, 2018;Soldatova et al, 2022;Zimmermann et al, 2022), has shown that during communication in the Internet space, we form a virtual or alternative identity. An alternative identity occurs when a user of social networks creates more than one pro le.…”
Section: Teenagers' Communication With Parents and Peers In Digital W...mentioning
confidence: 99%
See 2 more Smart Citations
“…Transformations related to the perceptual side of communication are of great interest. Research (Belinskaia, & Gavrichenko, 2018;Soldatova et al, 2022;Zimmermann et al, 2022), has shown that during communication in the Internet space, we form a virtual or alternative identity. An alternative identity occurs when a user of social networks creates more than one pro le.…”
Section: Teenagers' Communication With Parents and Peers In Digital W...mentioning
confidence: 99%
“…Parents, especially those with a low level of digital competence, have a more negative assessment of the impact of the online environment on their children's development. However, it is worth noting that, for both teenagers and parents, interpersonal interaction in the real world continues to play a much greater role than digital communication (Soldatova et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation